Case Report: Interferon- γ Rescues Monocytic Human Leukocyte Antigen Receptor (mHLA-DR) Function in a COVID-19 Patient With ARDS and Superinfection With Multiple MDR 4MRGN Bacterial Strains - Grimm, Clemens; Dickel, Steffen; Grundmann, Julian; Payen, Didier; Schanz, Julie; Zautner, Andreas Erich; Tampe, Björn; Moerer, Onnen; Winkler, Martin Sebastian (Frontiers in Immunology, 2021)
Background: CD14+ monocytes present antigens to adaptive immune cells via monocytic human leukocyte antigen receptor (mHLA-DR), which is described as an immunological synapse. Reduced levels of mHLA-DR can display an acquired immune defect, which is often found in sepsis and predisposes for secondary infections and fatal outcomes. Monocytic HLA-DR expression is reliably induced by interferon- γ (IFNγ) therapy. Case Report: We report a case of multidrug-resistant superinfected COVID-19 acute respiratory distress syndrome (ARDS) on extracorporeal membrane oxygenation (ECMO) support. The resistance profiles of the detected Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii and Citrobacter freundii isolates were equipped with resistance to all four antibiotic classes including carbapenems (4MRGN) and Cefiderocol in the case of K. pneumoniae. A causal therapeutic antibiotic strategy was not available. Therefore, we measured the immune status of the patient aiming to identify a potential acquired immune deficiency. Monocyte HLA-DR expression identified by FACS analysis revealed an expression level of 34% positive monocytes and suggested severe immunosuppression. We indicated IFNγ therapy, which resulted in a rapid increase in mHLA-DR expression (96%), rapid resolution of invasive bloodstream infection, and discharge from the hospital on day 70. Discussion: Superinfection is a dangerous complication of COVID-19 pneumonia, and sepsis-induced immunosuppression is a risk factor for it. Immunosuppression is expressed by a disturbed antigen presentation of monocytes to cells of the adaptive immune system. The case presented here is remarkable as no validated antibiotic regimen existed against the detected bacterial pathogens causing bloodstream infection and severe pneumonia in a patient suffering from COVID-19 ARDS. Possible restoration of the patient's own immunity by IFNγ was a plausible option to boost the patient's immune system, eliminate the identified 4MRGNs, and allow for lung recovery. This led to the conclusion that immune status monitoring is useful in complicated COVID-19-ARDS and that concomitant IFNγ therapy may support antibiotic strategies. Conclusion: After a compromised immune system has been detected by suppressed mHLA-DR levels, the immune system can be safely reactivated by IFNγ.